3D human motion analysis framework for shape similarity and retrieval - Slama, Rim; Wannous, Hazem; Daoudi, Mohamed (Image and vision computing, 2014)
3D shape similarity from video is a challenging problem lying at the heart of many primary research areas in computer graphics and computer vision applications. In this paper, we address within a new framework the problem of 3D shape representation and shape similarity in human video sequences. Our shape representation is formulated using extremal human curve (EHC) descriptor extracted from the body surface. It allows taking benefits from Riemannian geometry in the open curve shape space and therefore computing statistics on it. It also allows subject pose comparison regardless of geometrical transformations and elastic surface change. Shape similarity is performed by an efficient method which takes advantage of a compact EHC representation in open curve shape space and an elastic distance measure. Thanks to these main assets, several important exploitations of the human action analysis are performed: shape similarity computation, video sequence comparison, video segmentation, video clustering, summarization and motion retrieval. Experiments on both synthetic and real 3D human video sequences show that our approach provides an accurate static and temporal shape similarity for pose retrieval in video, compared with the state-of-the-art approaches. Moreover, local 3D video retrieval is performed using motion segmentation and dynamic time warping (DTW) algorithm in the feature vector space. The obtained results are promising and show the potential of this approach. [Display omitted] •A new framework is proposed for 3D human video analysis, based on a new descriptor called Extremal Human Curve.•Motion analysis is incorporated by employing motion segmentation into clips.•Clips are represented by trajectories on shape space.•Clip matching is performed using DTW on the manifold.•Summarization by clustering is exploited in content-based motion retrieval.